PROTEST MOVEMENTS ON LINKEDIN AS SPACE FOR CHALLENGING SOCIOTECHNICAL IMAGINARIES - Prá, Raquel; Antonello, Claudia Simone (AoIR Selected Papers of Internet Research, 2023)
The aim of this paper is to reflect on how the transformation of LinkedIn into an online environment from which are carried out critiques and questionings about the labor market, management practices, and work relations in Brazil, allow us to challenge sociotechnical imaginaries about the platform. The emergence of protest movements about circulating content on the platform reveals that, although certain technological configurations impose themselves on users, LinkedIn is not unique, universal, or deterministic, but multiple. This article addresses the technical issue, not yet properly explored by the ontological turn movement, discussing the protest movements on LinkedIn as a starting point for challenging pre-existing sociotechnical imaginaries, in order to boost societal change and new technological futures. The methodological strategy adopted to conduct the study was digital ethnography. Data collection, part of ongoing research, took place between March 2021 and February 2022. It includes news reports on LinkedIn and observations of posts on LinkedIn and discussions among members of a blog and a Facebook group gathered to conduct critiques of the content circulating on LinkedIn. Preliminary findings suggest that the movement of questioning from the platform itself seeks to appropriate the technological affordances and constraints imposed by LinkedIn to make it a space for awareness, problematization, and promotion of societal change. By establishing new uses for the platform, unrelated to the commercial objectives for which it was created, this movement gives conditions for the constitution of new sociotechnical imaginaries in relation to the platform itself and also, to rethink work relations.